LHS=sin^2x-cos^2x=(sinx+cosx)(sinx-cosx)
RHS=1-2sinxcosx
=(sin^2x+cos^2x)-2sinxcosx as sin^2x+cos^2x=1
=(sinx-cosx)^2
LHS and RHS can be equal only ifsinx+cosx=sinx-cosx
so it is not an identity
an identity must hole for all values
2006-11-09 13:41:39
·
answer #1
·
answered by raj 7
·
1⤊
0⤋
Gopal is right, but I suspect the original question was
(sin x - cos x)^2 = etc, and you made the mistake of thinking that you square each term separately. In fact, it should be
(sin x - cos x)(sin x - cos x) and when you expand you get four terms: sin x * each of the two terms in the second parentheses
-cos x * each of the two terms in the second parentheses.
Two of these four terms are
(sin x)^2 + (cos x)^2 which is identically equal to 1, and the other two give -2 sin x cos x. I leave you to finish it.
2006-11-09 21:56:10
·
answer #2
·
answered by Hy 7
·
0⤊
0⤋
( (sinx)(sinx) - ( cosx)(cosx) )
=( sinx + cosx )^2 -4sinxcosx [ (a^2-b^2) = (a+b)^2 - 4ab]
=sin^2x + cos^2x +2sinxcox - 4sinxcosx
= 1-2sinxcosx
Therefore it is an Identity
2006-11-09 22:01:26
·
answer #3
·
answered by Muskaan 1
·
0⤊
0⤋
if by this you mean
(sin(x) * sin(x)) - (cos(x) * cos(x))
(sin(x))^2 - (cos(x))^2
(1 - cos(x)^2) - cos(x)^2
1 - cos(x)^2 - cos(x)^2
1 - 2cos(x)^2
1 - 2cos(x)^2 = cos(2x)
--------------
1 - 2sinxcosx = 1 - sin(2x)
2006-11-09 22:23:55
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
loser. i don't care. go get a job. and if youre under 16 then you shouldn't be on this site, kiddo.
2006-11-09 21:35:31
·
answer #5
·
answered by ilina 2
·
0⤊
2⤋